2010
DOI: 10.1021/jp107755k
|View full text |Cite
|
Sign up to set email alerts
|

Water Dynamics in Bolaamphiphile Hydrogels Investigated by 1H NMR Relaxometry and Diffusometry

Abstract: The dynamical properties of water in hydrogels formed by the bolaamphiphiles dotriacontane-1,32-diyl-bis[2-(trimethylammonio)ethylphosphate] (PC-C32-PC) and its head group derivative dotriacontane-1,32-diyl-bis[2-(dimethylammonio)ethylphosphate] (Me(2)PE-C32-Me(2)PE) were investigated by determining the transverse relaxation times and the mean diffusion coefficients of the water protons. T(2) distributions obtained for hydrogels containing only 1 mg/mL of PC-C32-PC or Me(2)PE-C32-Me(2)PE were found to be almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A small part of the water molecules were hindered in their mobility by the hydrogel forming components. Immobilized water at the glass surface was seen around 300 ls in all samples (not shown), including the pure water sample (Bastrop et al 2011). The small peaks around 200 ms and at 380 ms in the hydrogel DS Ald ¼ 0:21 could origin in attached water molecules or hydrogen of oCS or CMCh.…”
Section: Homogeneity and Permeability Of The Hydrogelsmentioning
confidence: 86%
“…A small part of the water molecules were hindered in their mobility by the hydrogel forming components. Immobilized water at the glass surface was seen around 300 ls in all samples (not shown), including the pure water sample (Bastrop et al 2011). The small peaks around 200 ms and at 380 ms in the hydrogel DS Ald ¼ 0:21 could origin in attached water molecules or hydrogen of oCS or CMCh.…”
Section: Homogeneity and Permeability Of The Hydrogelsmentioning
confidence: 86%
“…Parameters measurable by LF-TD-NMR include self-diffusion coefficient ( D ), spin–lattice ( T 1 ), and spin–spin ( T 2 ) relaxation times. They are all extremely sensitive to changes in mobility of protons at different time scales and have been extensively employed to study other gels. …”
Section: Methodsmentioning
confidence: 99%
“…Diffusion coefficient studies have shown that the dynamic properties of water molecules in nanofibrous self-assembled hydrogels are almost unchanged compared to pure water22. Therefore, diffusion of protons and likely other analytes is highly feasible and unaltered in nanofibrous self-assembled hydrogels.…”
mentioning
confidence: 99%